Bioactive compounds from Bauhinia purpurea possessing antimalarial, antimycobacterial, antifungal, anti-inflammatory, and cytotoxic activities - Boonphong S. (2014)
Eleven new secondary metabolites (1-11), together with two known flavanones (12 and 13) and five known bibenzyls (14-18), were isolated from the root extract of Bauhinia purpurea. New compounds include eight dihydrodibenzoxepins (1-8), a dihydrobenzofuran (9), a novel spirochromane-2,1′-hexenedione (10), and a new bibenzyl (11). Antimycobacterial, antimalarial, antifungal, cytotoxic, and anti-inflammatory activities of the isolated compounds are reported, and biosynthetic pathways of these compounds are also discussed. © 2007 American Chemical Society and American Society of Pharmacognosy.